Phylogenetic hypotheses of octocoral species using predicted RNA secondary structures of the internal transcribed spacer 2 (ITS2) = - Hipótesis filogenética de especies de octocorales utilizando estructuras secundarias del espaciador interno transcrito 2 (ITS 2) (2006)
Octocoral systematics is a relatively new field of study. Morphological aspects together with molecular identification are tools that have been recently applied to solve systematic questions in octocorals due to their intricate morphology. For this group, as for many others, the use of a molecular marker that solves systematic problems at different taxonomic levels would be extremely useful for species identification and classification. Here we use the internal transcribed spacer 2 (ITS2) predicted RNA secondary structure for reconstructing phylogenetic hypotheses at different taxonomic levels. These structures are very important for the ribosome assembly since they are involved in mRNA folding and processing. For this reason, mutations that do not enable the proper folding of the sequence have to be compensated or suppressed. Hence, ITS2 are said to evolve in concert, which leads to a homogenization of all the copies of this gene throughout the genome...